The dual role of CXCL9/SPP1 polarized tumor-associated macrophages in modulating anti-tumor immunity in hepatocellular carcinoma - Yu Gu; Zhihui Zhang; Hao Huang; Wenyong Zhu; Hongjia Liu; Rongxin Zhang; Nan Weng; Xiao Sun (Frontiers in Immunology)
IntroductionThe main challenge for cancer therapy lies in immuno-suppressive tumor micro-environment. Reprogramming tumor-associated macrophages (TAMs) into an anti-tumor phenotype is a promising strategy.MethodsA comprehensive analysis by combing multi-regional single-cell, bulk and spatial transcriptome profiling with radiomics characterization was conducted to dissect the heterogeneity of TAMs and resolve the landscape of the CXCL9:SPP1 (CS) macrophage polarity in HCC.ResultsTAMs were particularly increased in HCC. SPP1+ TAMs and CXCL9+ TAMs were identified as the dominant subtypes with different evolutionary trajectories. SPP1+ TAMs, located in the tumor core, co-localized with cancer-associated fibroblasts to promote tumor growth and further contributed to worse prognosis. In contrast, CXCL9+ TAMs, located in the peritumoral region, synergized with CD8+ T cells to create an immunostimulatory micro-environment. For the first time, we explored the applicability of CS polarity in HCC tumors and revealed several key transcription factors involved in shaping this polarity. Moreover, CS polarity could serve as a potential indicator of prognostic and micro-environmental status for HCC patients. Based on medical imaging data, we developed a radiomics tool, RCSP (Radiogenomics-based CXCL9/SPP1 Polarity), to assist in non-invasively predicting the CS polarity in HCC patients.ConclusionOur research sheds light on the regulatory roles of SPP1+ TAMs and CXCL9+ TAMs in the micro-environment and provides new therapeutic targets or insights for the reprogramming of targeted macrophages in HCC.